Analisis Kemampuan Pemahaman Konsep Matematis Peserta Didik Ditinjau Dari Gender - Nurani, Zulfa; Merliza, Pika (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to determine the ability to understand mathematical concepts of high school students in terms of gender in polynomial material. This research is a qualitative descriptive study. Data collection was carried out in class XI MIA, totaling 36 consisting of 14 male students and 22 female students at Bangun Cipta Rumbia High School for the 2023/2024 academic year. Data collection was carried out by tests and interviews. The interviews conducted by researchers used 6 subjects as representatives consisting of 3 male subjects and 3 female subjects with the criteria of high, medium and low comprehension ability. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions/verification. The triangular method is used to test the validity of research data by comparing test and interview results. The results of this research show that the ability to understand mathematical concepts of class XI MIA students has an average percentage in the low category reaching 58.3%. Male students in the high and medium categories understand mathematical concepts better than females. The indicators of low category students' ability to understand concepts have not been fully achieved because they have not been able to describe the problem completely.